Application value of 18F-FDG PET/CT in primary spleen angiosarcoma with liver metastasis: a case report and literature review - Shao, Mingyan; Qi, Wanling; Xu, Rong; Luo, Zhehuang; Liao, Fengxiang; Fan, Sisi (Frontiers in Oncology, 2024)
Background:Primary splenic angiosarcoma(PSA) is rare in clinical. It is a malignant tumor derived from the endothelial cells of the splenic sinuses.PSA has unknown etiology, high malignancy degree, easy early metastasis, atypical clinical symptoms and imaging findings, and difficult early diagnosis. This paper reports the 18F-FDG PET/CT findings of a case of PSA with intrahepatic metastasis, summarizes its clinical, imaging and pathological data, and reviews the literature. Case description:A 64-year-old male patient presented with left lower abdominal distending pain without obvious causes on 2022-03-13. The pain was persistent dull and worsened after sitting and eating.Blood routine examination showed: RBC↓3.33×1012/L, WBC↑12.32× 109 /L, PLT↓40×109 /L.Tumor markers:CA125↑47.0 U/ml , AFP(-),CEA(-),CA199(-),CA724(-).Non-contrast enhanced CT scan of the abdomen showed the spleen was significantly enlarged in volume, irregular in shape, multiple nodules and clumpy low-density shadows, unclear boundaries, uneven density, and multiple necrosis.Enhanced CT showed diffuse uneven mild enhancement of spleen, and the degree of enhancement increased with time.Multiple nodular low-density shadows were seen in the liver, which were slightly enhanced by enhanced scan.18F-FDG PET/CT showed multiple nodular and massive lesions in the spleen with multiple necrotic areas.There were multiple nodular lesions in the liver, the level of FDG metabolism increased, the SUVmax of spleen lesions was 9.0, and the SUVmax of liver lesions was 5.6. 18F-FDG PET/CT diagnosis of splenic malignancy with liver metastasis.Finally, after multidisciplinary discussion, it was decided to perform laparoscopic total splenectomy and portal vein infusion chemotherapy.Pathological examination showed that the tumor cells were round, oval or fusiform, with obvious atypia, arranged into cable or anastomosed vascular lumen.The diagnosis was Primary splenic angiosarcoma with massive necrosis.After surgery, the patient received anti-tumor combined therapy and died 5 months later. Conclusion: The incidence of PSA is very low, and its clinical and radiological manifestations lack specificity. 18F-FDG PET/CT imaging has a certain diagnostic value for PSA and significant utility in preoperative staging, guiding biopsy procedures, evaluating postoperative treatment response, and monitoring disease recurrence. PSA should be considered in the presence of a space-occupying lesion within the spleen that exhibits necrotic areas, shows progressive enhancement on contrast-enhanced scans, and demonstrates heterogeneous increases in FDG uptake.